TINJAUAN HUKUM DOKTER YANG BERKOLUSI DENGAN PERUSAHAAN FARMASI DALAM MERESEPKAN OBAT - Yenny Fitri Z (JCH (Jurnal Cendekia Hukum), 2018)
At the end of 2015, the Tempo Magazine investigation team released a gratification case conducted by the pharmaceutical company Interbat against 2,125 doctors. The gratuities are suspected to be one of the reasons that influence doctors in prescribing drugs to patients. Funds used by pharmaceutical companies to serve doctors can reach 45 percent of drug prices. Therefore, patients must redeem the drug at a more expensive price. Moving from the results of these investigations, the authors are interested to examine criminal rules that can ensnare doctors who receive the gift from pharmaceutical companies. So far, the rule of law governing the prohibition of doctors receiving gifts from Pharmaceutical Companies has not had a deterrent effect. The existing arrangements are in the realm of ethics and administration. As a result, the cooperation of doctors and pharmaceutical companies in prescribing the drug continues and affects the patient's harm. Because in the practice of the physician profession is divided into two, namely private doctors and civil servants, then the formulation of the issues to be discussed in this paper is, First, how the imposition of legal sanctions for private doctors who receive the gift from Pharmaceutical Company Second, how the imposition of legal sanctions for civil servant doctors who receive the gift from Pharmaceutical Company To answer the problem, the author uses normative juridical research method. The results of his research are private doctors who receive the gift from pharmaceutical companies may be subject to Article 3 of Law Number 11 Year 1980 on the Crime of Bribery. As for doctors who have the status of Civil Servants subject to Article 12B of Law Number 31 Year 1999 junto Law Number 20 Year 2001 About Corruption Eradication (Anti-Corruption Law). As a suggestion at the end of the writing, the author wants that the formulation of Article 12B of the Anti-Corruption Law be expanded so that it is not limited to civil servants or state officials only. However, pending the improvement of the formulation of Article 12B, the authors recommend that law enforcement still play an active role by using Article 3 of the Anti-Bribery Law to ensnare doctors who receive the gift from ph armaceutical companies.